PARÍS, CAPITAL DEL SIGLO XIX - Tomás Ucedo, José María (Universidad de Costa Rica, 2023)
In this article, the author proposes to re-examine the fundamental topics of Walter Benjamin’s thought along the articulation of three dimensions: modern experience, the city and technology. These dimensions point to an aesthetic reflection that is attached to the development of urban space in Paris of the Nineteenth Century.